Предмет: Алгебра,
автор: Turiwer14
Помогите решить уравнение!!Плиз!!
(x-3)² + (3-x) × (x+3)=(x+2)² - x².
Плиз!!
Ответы
Автор ответа:
0
(x-3)²+(3-x)*(x+3)=(x+2)²-x²
x²-6x+9+9-x²=x²+4x+4-x²
-6x-4x=4-9-9
-10x=-14|:(-10)
x=1,4
Ответ:1,4
x²-6x+9+9-x²=x²+4x+4-x²
-6x-4x=4-9-9
-10x=-14|:(-10)
x=1,4
Ответ:1,4
Похожие вопросы
Предмет: Английский язык,
автор: azara47
Предмет: История,
автор: petey1111
Предмет: Литература,
автор: makcimmelnik222
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: Xuli9311